Active Receptivity: The Positive, Mindful Flow of Mental Energy - Terri G. Pullen (Journal of the Assembly for Expanded Perspectives on Learning, 1997)
The construct of mindfulness relates to Eastern meditative practices, consciousness, quantum physics, and creativity.